An East Indian wedding, Trinidad - (:unkn) unknown (My University, 2009)
A group of musicians of East Indian origin sitting cross legged at a wedding while the lone woman in the group is seated on a stool.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Postcards; Trinidad and Tobago; Indian musicians--Trinidad and Tobago; Weddings--Trinidad and Tobago; East Indians--Trinidad and Tobago; Male musicians--Trinidad and Tobago; Marriage customs and rites--India; Men--Trinidad and Tobago; Ethnic costume--India